2018
DOI: 10.1111/tpj.14041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics analyses reveal the molecular roadmap and long non‐coding RNA landscape of sperm cell lineage development

Abstract: Sperm cell (SC) lineage development from the haploid microspore to SCs represents a unique biological process in which the microspore generates a larger vegetative cell (VC) and a smaller generative cell (GC) enclosed in the VC, then the GC further develops to functionally specified SCs in the VC for double fertilization. Understanding the mechanisms of SC lineage development remains a critical goal in plant biology. We isolated individual cells of the three cell types, and characterized the genome-wide atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 86 publications
(126 reference statements)
3
20
0
Order By: Relevance
“…Specifically, for A. thaliana the co-expression network revealed that cluster C5 (sperm) is not well connected with other clusters (Fig. 6b), suggesting that the sperm cell transcriptome is distinctive, confirming earlier observations [58][59][60][61] . The connections between clusters followed a pattern from cluster C0…”
Section: Analysis Of Signaling Network Underpinning Male Gametophytesupporting
confidence: 86%
“…Specifically, for A. thaliana the co-expression network revealed that cluster C5 (sperm) is not well connected with other clusters (Fig. 6b), suggesting that the sperm cell transcriptome is distinctive, confirming earlier observations [58][59][60][61] . The connections between clusters followed a pattern from cluster C0…”
Section: Analysis Of Signaling Network Underpinning Male Gametophytesupporting
confidence: 86%
“…The asymmetric microspore division accompanies the loss of pluripotency and leads to its daughter cells' distinct fate and identity. Our study has demonstrated that the asymmetric division is followed by global repression of genes associated with cell pluripotency and somatic development (Liu et al ., 2018). Several evidence lines have shown that decreased DNA methylation might promote the microspore's embryogenesis initiation in Brassica and triticale (Solís et al ., 2012, 2015; Nowicka et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the identity of the GC and SCs is another concerning issue in reproduction biology. We revealed that the GC and SCs had nearly identical DNA methylome, which is compatible with previous transcriptome and proteome studies that showed that SCs had similar proteome and transcriptome, and almost identical histone profiles with the GC (Zhao et al ., 2013; Yang et al ., 2016; Liu et al ., 2018). These data indicate that the central landscape of molecular features in SCs may have been already established in the GC and is transmitted to SCs via GC mitosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations